Kefir Improves the Efficacy and Tolerability of Triple Therapy in Eradicating Helicobacter pylori - YILMAZ, YUSUF (MARY ANN LIEBERT, INC, 2011)
Preliminary evidence has suggested that probiotics may improve eradication rates in patients infected with Helicobacter pylori treated by triple therapy. This study examined the effect of combining triple therapy with kefir, a fermented milk drink containing probiotics. A randomized, double-blind study was carried out on 82 consecutive patients with symptoms of dyspepsia and H. pylori infection confirmed by the urea breath test. Patients were given a two times a day, 14-day course of lansoprazole (30 mg), amoxicillin (1,000 mg), and clarithromycin (500 mg) with either 250 mL of kefir twice daily (triple therapy + kefir, n = 46) or 250 mL of milk containing placebo (triple therapy + placebo, n 36). Side effects were determined using a standard questionnaire form at 15 days after beginning treatment. Patients returned for urea breath tests 45 days after beginning treatment. Significantly more triple therapy + kefir patients achieved eradication (36 of 46 [78.2%]) compared with triple therapy + placebo patients (18 of 36 [50.0%]) (P.026, chi(2) test). Side effects were significantly less frequent and less severe in triple therapy + kefir patients than in triple therapy + placebo patients. We conclude that a 14-day regimen of triple therapy with kefir is more effective in achieving H. pylori eradication than is triple therapy alone.
Keywords: Helicobacter pylori; kefir; triple therapy; PROBIOTIC PREPARATIONS; INFECTION; YOGURT; SUPPLEMENTATION; METAANALYSIS; RESISTANCE; DISEASES; GRAINS